With me or against me: tumor suppressor and drug resistance activities of SAMHD1 - Herold, Nikolas; Kutzner, Juliane; Schaller, Torsten (Experimental hematology, 2017)
Sterile alpha motif and histidine/aspartic acid domain-containing protein 1 (SAMHD1) is a (deoxy)guanosine triphosphate (dGTP/GTP)-activated deoxyribonucleoside triphosphate (dNTP) triphosphohydrolase involved in cellular dNTP homoeostasis. Mutations in SAMHD1 have been associated with the hyperinflammatory disease Aicardi-Goutières syndrome (AGS). SAMHD1 also limits cells' permissiveness to infection with diverse viruses, including human immunodeficiency virus (HIV-1), and controls endogenous retroviruses. Increasing evidence supports the role of SAMHD1 as a tumor suppressor. However, SAMHD1 also can act as a resistance factor to nucleoside-based chemotherapies by hydrolyzing their active triphosphate metabolites, thereby reducing response of various malignancies to these anticancer drugs. Hence, informed cancer therapies must take into account the ambiguous properties of SAMHD1 as both an inhibitor of uncontrolled proliferation and a resistance factor limiting the efficacy of anticancer treatments. Here, we provide evidence that SAMHD1 is a double-edged sword for patients with acute myelogenous leukemia (AML). Our time-dependent analyses of The Cancer Genome Atlas (TCGA) AML cohort indicate that high expression of SAMHD1, even though it critically limits the efficacy of high-dose ara-C therapy, might be associated with more favorable disease progression.
Gesehen am 07.06.2018
Available online 11 May 2017